Hip Abduction Can Prevent Posterior Edge Loading of Hip Replacements - van Arkel, Richard J (Blackwell Publishing Ltd, 2013)
Edge loading causes clinical problems for hard-on-hard hip replacements, and edge loading wear scars are present on the majority of retrieved components. We asked the question: are the lines of action of hip joint muscles such that edge loading can occur in a well-designed, well-positioned acetabular cup? A musculoskeletal model, based on cadaveric lower limb geometry, was used to calculate for each muscle, in every position within the complete range of motion, whether its contraction would safely pull the femoral head into the cup or contribute to edge loading. The results show that all the muscles that insert into the distal femur, patella, or tibia could cause edge loading of a well-positioned cup when the hip is in deep flexion. Patients frequently use distally inserting muscles for movements requiring deep hip flexion, such as sit-to-stand. Importantly, the results, which are supported by in vivo data and clinical findings, also show that risk of edge loading is dramatically reduced by combining deep hip flexion with hip abduction. Patients, including those with sub-optimally positioned cups, may be able to reduce the prevalence of edge loading by rising from chairs or stooping with the hip abducted. © 2013 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 31:1172–1179, 2013.